How Perceived Institutional Forces Impact ERP (Enterprise Resource Planning) Implementers When Assimilating an ERP Solution in a Public Sector Organisation - Orr, Gilbert Duncan (Auckland University of Technology, 2022)
This research aimed to explore how perceived institutional forces impact ERP implementers when assimilating an ERP solution in a public sector organisation in New Zealand. A public sector organisational setting was chosen as the human resource structure of government agencies tends to be more complex, with wider levels of executives and groups tending to interpret business processes, rules and guidelines in varied ways. This more complex organisational human resource composition with added levels of administration is often underestimated by leaders in terms of getting buy in from affected staff that in turn, impedes an organisations agility. This method of operating inherently overflows into the organisational culture and in doing so, makes it more challenging to determine accepted values and perspectives to guide expected conduct and behaviours. The study illustrates how the period after an ERP solution is technically implemented, but not yet assimilated throughout the organisation, is a time where ERP implementors particularly leadership, must come to the fore. It is at this stage that leaders receive direct feedback of whether the earlier investment in reviewing, preparing and revamping the organisational culture to assist manage the many changes that a new ERP solution brings, has been successful or not. The study identifies a myriad of often inter-linked themes centred on the institutional environment, leadership and managing change for why differing levels of staff actively support (or not) the adoption of the new ERP solution. In contrast to quantitative and survey data, this qualitative study, using semi-structured interviews, provides a direct line to the key people in public sector organisations who were actively involved in implementing and/or assimilating ERP solutions. It gives an insight into the challenges faced by ERP implementors when leading organisational wide change, whilst introducing a new strategic IT solution across a variety of public sector organisations. The findings have practical implications. The study shows that where an organisations culture is agile and facilitates change, where the ERP solution is seen as a strategic investment and leadership drives change, the assimilation processes of an ERP solution tend to be embedded more quickly and successfully. ERP implementors can leverage the key and sub themes that emerged from the findings as practical examples of where they might best focus their involvement and attention prior to and whilst undertaking ERP assimilation across public sector organisations.